Election Dynamics In Indonesia The First Election Era Of 1955 - Ruhdiara Ruhdiara; Agus Junaidi; Siti Fatimah (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2022)
General elections are a form of democracy organized by the government for the benefit of the people. With the general election, the people participate in providing their political aspirations which are intended to elect their representatives in the government. The general election is the right step taken by the government to implement the principle of people's sovereignty which has been stated in the provisional constitution. In order to perfect the provisional constitution and to elect representatives to sit in Parliament, the Indonesian government held the first general election in 1955. The type of research used in this research is classified as library research. namely research in which data is processed and extracted from various books, newspapers, magazines and several articles that are related to this research. Then the approach used is a historical approach (historical research). While the method used in the research is a descriptive qualitative research method. The results of the research show that Liberal Democracy in Indonesia was expected from 1950 to 1959, in practice the government system adheres to a parliamentary system. This democracy has a very strong characteristic regarding the multi-party system that is adopted, but there is no political party that has an absolute majority. In this system, the age of the cabinet in each government is very short, causing frequent cabinet changes. At this time the second major achievement after the proclamation was successfully obtained was the achievement of the General Election in 1955 whose participants came from various parties that existed at that time in Indonesia. This election was successfully carried out in two stages, namely the first stage on September 29, 1955 holding the election for the DPR and on December 15, 1955 holding the election for Members of the Constituent Assembly. The top four winners of the 1955 election included: PNI, Masyumi, NU and PKI.Pemilihan umum merupakan salah satu bentuk demokrasi yang diselenggarakan oleh pemerintah untuk kepentingan rakyat. Dengan adanya pemilihan umum, masyarakat ikut serta memberikan aspirasi politiknya yang dimaksudkan untuk memilih wakil-wakilnya dalam pemerintahan. Pemilihan umum merupakan langkah tepat yang diambil pemerintah untuk melaksanakan prinsip kedaulatan rakyat yang telah tertuang dalam undang-undang dasar sementara. Untuk menyempurnakan konstitusi sementara dan untuk memilih perwakilan untuk duduk di DPR, pemerintah Indonesia mengadakan pemilihan umum pertama pada tahun 1955. Jenis penelitian yang digunakan dalam penelitian ini adalah penelitian kepustakaan. yaitu penelitian yang datanya diolah dan disarikan dari berbagai buku, surat kabar, majalah dan beberapa artikel yang berhubungan dengan penelitian ini. Kemudian pendekatan yang digunakan adalah pendekatan sejarah (historis research). Sedangkan metode yang digunakan dalam penelitian ini adalah metode penelitian deskriptif kualitatif. Hasil penelitian menunjukkan bahwa Demokrasi Liberal di Indonesia berlangsung dari tahun 1950 hingga 1959, dalam prakteknya sistem pemerintahan menganut sistem parlementer. Demokrasi ini memiliki ciri yang sangat kuat mengenai sistem multi partai yang dianut, namun tidak ada partai politik yang memiliki mayoritas mutlak. Dalam sistem ini, umur kabinet di setiap pemerintahan sangat singkat sehingga sering terjadi pergantian kabinet. Pada saat ini prestasi besar kedua setelah proklamasi berhasil diperoleh adalah prestasi Pemilihan Umum tahun 1955 yang pesertanya berasal dari berbagai partai yang ada saat itu di Indonesia. Pemilihan ini berhasil dilaksanakan dalam dua tahap, yaitu tahap pertama pada 29 September 1955 menyelenggarakan pemilihan DPR dan pada 15 Desember 1955 menyelenggarakan pemilihan Anggota Konstituante. Empat besar pemenang pemilu 1955 antara lain: PNI, Masyumi, NU dan PKI.